GRAIN CHEMICAL COMPOSITION OF DENTS, POPPING MAIZE AND SWEET MAIZE GENOTYPES - Radosavljević, Milica (Journal on Processing and Energy in Agriculture, 2020)
Maize is one of the most important field crops both in the world and in our country. All commercially grown maize hybrids can be classified into one of five elementary types: dent, flint, floury, popping and sweet maize hybrids. This paper presents results of grain chemical compositions of different maize genotypes. The results show that contents of starch, protein, oil, crude fibre, and ash of grains of yellow- and white-seeded dents, popping and sweet maize genotypes ranged in the intervals: 53.54-68.13%; 9.19-13.00%; 4.35-5.39%; 2.13-3.93% and 1.28-2.85%, respectively. The ratio of amylose to amylopectin of starch of observed genotypes varied from 21:79 to 28:72. The content of lignocellulosic fibres: NDF, ADF, ADL, hemicellulose and cellulose ranged from 11.31-15.27%; 2.51-3.54%, 0.24-0.52%, 8.10-12.68% and 2.14-3.02%, respectively. The contents of NFC and NFE varied from 67.16 to 73.97% and from 74.83 to 83.05%, respectively. The solubility index of albumin, globulin, zein and glutelin ranged from 9.46-29.42%, 5.64-13.13%, 21.11-28.10% and 18.81-23.69%, respectively.
Keywords: maize, grain, chemical composition